2016
DOI: 10.1002/2016ja022511
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated observations of F region 3 m field‐aligned plasma irregularities associated with medium‐scale traveling ionospheric disturbances

Abstract: Three meter field‐aligned irregularities (3 m FAIs) associated with medium‐scale traveling ionospheric disturbances (MSTIDs) that occurred on 5 February 2008 were observed by using the Chung‐Li 52 MHz coherent scatter radar. Interferometry measurements show that the plasma structures responsible for the 3 m FAI echoes are in a clumpy shape with a horizontal dimension of about 10–78 km in a height range of 220–300 km. In order to investigate the dynamic behaviors of the plasma irregularities at different scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…While the prereversal enhancement occurs, the enhanced eastward electric field will raise the height of ionosphere, steepen the density gradient in the bottomside F region, and so create the favorable conditions for RT instability [ Chiu and Straus , ; Ossakow , ]. Another is attributed to the gradient drift instability associated with the medium‐scale traveling ionospheric disturbances (TIDs) [ Lin et al ., ]. The SpreadF Experiment carried out in Brazil indicated that the gravity wave‐induced TIDs have the ability to seed the RT instability and the following plasma bubbles extending to higher altitudes [ Abdu et al ., ; Fritts et al ., ].…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the prereversal enhancement occurs, the enhanced eastward electric field will raise the height of ionosphere, steepen the density gradient in the bottomside F region, and so create the favorable conditions for RT instability [ Chiu and Straus , ; Ossakow , ]. Another is attributed to the gradient drift instability associated with the medium‐scale traveling ionospheric disturbances (TIDs) [ Lin et al ., ]. The SpreadF Experiment carried out in Brazil indicated that the gravity wave‐induced TIDs have the ability to seed the RT instability and the following plasma bubbles extending to higher altitudes [ Abdu et al ., ; Fritts et al ., ].…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…The strong photoionization after sunrise is unfavorable for the formation of steep electron density gradient and polarized electric fields. It is very difficult for the plasma bubbles to be produced in the sunlit ionosphere, whether the RT instability, the gravity waves, the transequatorial wind, or the collisional shear instability is working [ Maruyama , ; Hysell et al ., , ; Saito et al ., ; Abdu et al ., ; Li et al ., ; Tsunoda , ; Lin et al ., ]. However, once the nighttime plasma bubbles are produced, they can survive in the sunshine for a relatively long period.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…present in this region can be detected by the radar. In light of the fact that the measured phase differences between different receiving channels contain the system phase bias, a comparison of the radar-measured phase differences and IGRF-12-calculated phase differences can deduce the radar system phase offsets (Chu and Wang 1997;Wang 1999;Lin et al 2016). Figure 2 shows its expected echoing regions for the years of 1986 and 2018, in which the FAI height range of 100 -110 km and aspect angle of 0.1° are given to calculate the echoing region from IGRF-12 model.…”
Section: Ionospheric Fai Methodsmentioning
confidence: 99%
“…The locations of the 3-m FAIs in the echoing region can be identified and positioned from their echoes by using interferometry technique. The elevation angle i and azimuth angle z can be estimated from the phase differences of the FAI echoes detected by different receiving channel pairs in accordance with following equations (Chu and Wang 1997;Lin et al 2016)…”
Section: Ionospheric Fai Methodsmentioning
confidence: 99%
“…Radar interferometry (RI) has been widely used in atmospheric studies such as mean angle of arrival of radar echoes [26], lightning detection [27], meteor radar wind [28], among others. Use of RI in measurement of the aspect angle of FAIs was first reported by Kudeki and Farley in 1989 [3] for the equatorial electrojet region.…”
Section: Radar Interferometrymentioning
confidence: 99%